Besinning oor die interpretasie van die geloof wat in die belydenis van die maagdelike verwekking van Jesus geleer word 1 - Aarde, Andries van (Hervormde teologiese studies, 2000)
Interpreting the doctrine of the virginal conception of Jesus. The aim of this article is to relect on the hermeneutical premises related to doctrinal criticism. The dogma of the virginal conception of Jesus as recorded in the Heidelberg Catechism and the Belgic Confession serves as case study. The article argues that the same historical critical exegetical principles applied to Scripture should guide the interpretation of creeds. Christian doctrine should be seen as a social demarcator, grounded in the foundational narrative of Jesus of Nazareth. This foundational narrative is interpreted by means of doctrinal criticism when doctrine is seen as the interpretation of the experience of belief and as the articulation of truth.